Konsep Kesejahteraan Dalam Ekonomi Islam (Perspektif Maqasid Asy-Syari’ah) - Martini Dwi Pusparini (University of Darussalam Gontor, 2015)
The concept of welfare as a goal in the conventional economy turns a terminology that is controversial, because it can be defined by a lot of understandings. One of them is purely materialist understanding completely deny the spiritual connection, or perhaps with a slight allusion to the spiritual aspect. If welfare is defined by the materialistic and hedonistic concept, then the economics provide a portion of excellence in the fulfillment of self-interest and maximize wealth, physical pleasure, and satisfaction of lust. Islamic economic view of the overall well-being is based on Islamic teachings about life. This concept is very different from the concept of well-being in the conventional economy, because it is a holistic concept. Welfare are essential within the framework of the Shari’ah is not always realized by concentrating on efforts to maximize wealth and consumption; it requires both material and spiritual fulfillment of human needs that are closely intertwined, fight for a balance between individual and social interests, and actualize Maqasid ash-Shariah. Islamic social welfare function is a concept rooted in socio-economic thought of Al-Ghazali. He identified all problems, whether in the form masalih (utilities, benefits) and mafasid (disutility, damage) in improving social welfare. He also explained in more detail that sharia objectives is to improve the welfare of all human beings, which lies in the protection of the faith (al-din), soul (al-nafs), intellect (alaql), descent (al-nasl), and wealth (al-mal). Anything that ensure the protection of this fifth guarantee the public interest and is desirable.